Precision management of groundwater abstraction on different spatial scales of lower Chenab canal system in Punjab, Pakistan. Issue 17 (2018) - Yongguang, Hu; Buttar, Noman Ali; Shabbir, Abdul; Faheem, Muhammad; Aleem, Muhammad
Abstract: The estimation of groundwater abstraction at different spatial scales of lower canal system in Punjab, Pakistan was made for Khurianwala and Mungi distributaries to quantify groundwater abstraction, during 2014-2015 to identify the share of canal water in relevance to groundwater, to minimize the crop water demand and to access the constraints in the implementation of demand-based irrigation system in lower Chenab canal system. Information in survey captured on a questionnaire including Bore depth, Water table depth, Head range, Diameter of pipe, Brand of the pump, Water quality, Pumping hours for the whole year and cost of tube well installation was obtained during this survey. This abstraction data calculated through the ground trothing was corroborated and reconfirmed through R.S and GIS. After review of the literature, analysis of the situation & interpretation of results, it revealed that Ground water abstraction is significantly higher at the tail of the distributary especially at peak months. Moreover, Groundwater intensive survey gave much better estimation and an assessment on quantification of groundwater abstraction and sharing on canal water. Constraints for the adoption of demand based irrigation system were also studied to make recommendations.